A randomized, double-blind, single-dose, parallel phase I clinical trial to compare the bioequivalence, immunogenicity, and safety of bevacizumab biosimilar and bevacizumab in healthy Chinese subjects. (3rd August 2022) - Liu, Zhengzhi; Gao, Zhenyue; Yang, Wei; Zhang, Lixiu; Xiao, Nan; Qu, Dongmei; Su, Zhengjie; Xu, Kaibo; Liu, Guangwen; Wang, Yanli; Ren, Qing; Yu, Shuang; et al.
ABSTRACT: Background: Bevacizumab, a humanized monoclonal antibody against VEGF, can be used as a target therapy for colorectal cancer. A phase I clinical trial was conducted to compare the bioequivalence, immunogenicity, and safety of bevacizumab biosimilar (Chia Tai Tianqing Pharmaceutical Group Co., Ltd.) and Bevacizumab (Roche Diagnostics GmbH) in healthy Chinese males. Research design & method: Healthy Chinese subjects (N = 98) were randomly divided into two groups. A single-dose bevacizumab biosimilar or Bevacizumab was given per cycle. Plasma drug concentrations were detected by liquid chromatography–tandem mass spectrometry (LC-MC/MS) assay. We detected the levels of anti-drug antibody (ADA) to evaluate drug immunogenicity and the safety of drugs throughout the study. Results: The geometric mean ratios (GMRs) of AUC0-t, Cmax, and AUC0-∞ for bevacizumab biosimilar and Bevacizumab were 96.27%, 93.69%, and 97.01%, respectively. The 90% CIs were all within 80–125%, meeting the bioequivalence standards. The levels of ADA were similar. In addition, the two drugs both demonstrated excellent safety in the trial. Conclusion: This study showed that bevacizumab biosimilar and Bevacizumab had similar pharmacokinetics (PK) parameters and safety in healthy Chinese subjects.